Hydroxychloroquine as Therapeutic Option in COVID-19: Analysis of Suspected Cardiovascular Adverse Drug Events Reported in the VigiBase (Bangladesh Journal of Medical Science, 2021)
Background: Hydroxychloroquine(HCQ), one of the repurposed drugs in COVID-19, has several known cardiovascular(CVS) toxicities.Methods: VigiBase data were used to analyze the reported ADEs linked to HCQ. The data were analyzed based on age, gender, and seriousness of ADEs at the System Organ Classification level and the individual Preferred Term level.Results: The majority were above 18 years(91.6%) and from Europe(41.6%). A total of 5,315 ADEs were associated with HCQ use in COVID-19. Of these, 918 ADEs were attributed to CVS and reported from 773 patients. Grossly, CVS ADEs were associated with concomitant use of HCQ and azithromycin(AZM), and only 40 ADEs were solely due to HCQ. The majority were serious (69.3%) and resolved afterward (51%). In CVS ADEs, there were 366 cardiac disorders, 38 vascular disorders, and 514 ADEs under investigation. Among the cardiac disorders, palpitation was the most typical (N=65), followed by bradycardia(N=44) and tachycardia(N=33). Among arrhythmias, QT prolongation (N=469), atrial fibrillation (N=25), and ventricular tachycardia(N=16) were common. The odds of developing serious CVS ADEs increased with age, patients aged 45-64 years(OR=1.75; p= 0.015) and >65 years(OR=1.93, p=0.003) as compared to younger ones.Conclusion: Hydroxychloroquine with known CVS toxicities and increased risk with co-administering AZM makes physicians cautious while prescribing in COVID-19 patients.Bangladesh Journal of Medical Science Vol.20(4) 2021 p.897-910